Repayment versus investment conditions and exclusivity in lending contracts - Spiros P. Bougheas; Indraneel Dasgupta; Oliver Morrissey (Institute for the Study of Labor (IZA), 2009)
Lenders condition future loans on some index of past performance. Typically, banks condition future loans on repayments of earlier obligations whilst international organizations (official lenders) condition future loans on the implementation of some policy action ('investment'). We build an agency model that accounts for these tendencies. The optimal conditionality contract depends on exclusivity - the likelihood that a borrower who has been denied funds from the original lenders can access funds from other lenders.
Keywords: G21; F34; 330; Long-term loans; investment conditions; repayment conditions; exclusivity; Kreditgeschäft; Konditionen; Kreditwürdigkeit; Anpassungsprogramm des IWF; Anreizvertrag; Agency Theory; Theorie